Thermal Analysis of Indirect Double-sided Cooling Power Modules Considering the Impact of ThermalInterface Material Characteristics - So, Ji-Yong; Yoon, Young-Doo; Yoon, SangWon (Journal of semiconductor technology and science, 2025)
The automotive industry is advancing toward eco-friendliness, with an increasing number of xEV models entering the market. This shift drives demand for high-performance power semiconductors, leading to greater power density and heat generation, which challenge the thermal performance of xEV power modules, which is the core energy-conversion component. To address these challenges, advanced module cooling structures, such as direct single-sided and double-sided cooling (DSC), have been developed. However, most DSC power modules rely on indirect cooling using thermal interface materials (TIMs), whose low thermal conductivity limits thermal performance improvements despite the use of complex 3D structures. This study investigates the impact of TIM characteristics on the thermal resistance of power modules. Finite element analysis (FEA) simulations demonstrate an obvious reduction in thermal resistance with enhanced TIM conductivity, revealing a performance saturation point beyond a certain conductivity level. These findings would provide valuable insights for TIM design targets. KCI Citation Count: 0